Penstrukturan data bagi video asas menggunakan kaedah formal untuk pengekstrakan dan perbandingan video - Fadilah Harun
A multimedia database is a structure and composition of multimedia information forcontent retrieval. It supports various multimedia data types such as text, images,audio and video. Among all these types of data media, video is the most challenging.This is because the video incorporates all the information from different media typesinto a single data stream. Multimedia data manipulation is not as easy as using aconventional database. The database can display video clearly, but their problem isto achieve the video data structure itself. This problem occurs when we want toensure that content data in the database similar with the content specified in thequery. Based on previous studies, there are several techniques for structuring datavideo such as temporal and spatial relationships. All these techniques focused on thedesign of a good database. However, structuring a video data have some limitations,such as the size and complex object model in a variety of conditions make it difficultto index, search and retrieval of video content. To realize this study, formal methodapproach will be used to determine the relationship and retrieve the contents of thestructure. This study resulted in a framework known as Video Extraction Analyzerv